(untitled) (Solukhumbu Multiple Campus Research Journal, 2024)
The modern lifestyle is accompanied by a great amount of stress, and private school teachers are also not far from it. The workplace is also more stressful than it used to be. Stress among private school teachers is influenced by a multifaceted phenomenon. For the completion of this research, the predetermined objectives were set first. The objectives of this study were to analyze and address the factors contributing to stress among private school teachers in order to implement effective support mechanisms and promote overall well-being within the educational environment. Altogether, 19 respondents, among them 1 principal, 2 management committee members, and 16 teachers (8 from the basic level and 8 from the secondary level) of a private school in Solukhumbu, were selected purposefully. The data and responses were collected from management committee members, principal, and teachers through an open ended questionnaire, and the responses were interpreted and described qualitatively according to the defined objectives. Maslow’s hierarchy of needs theory is interconnected in this study to understand stress among private school teachers and use appropriate remedies in a specific order, starting with basic physiological needs and progressing to higher-level needs. 16 respondents working as a school teacher in a private school were burdened with excessive tasks, responsibilities, and demands within their professional role. They were facing high teaching loads with numerous classes, subjects, and students to manage. They had very limited time for lesson preparation and other innovations. Strategies such as workload management, providing adequate resources, promoting work-life balance, and offering support for professional development can help alleviate the stress associated with work overload and enhance the quality of teaching and learning. Further, private school teachers in Solukhumbu were not getting the facilities of professional development opportunities like seminars, workshops, research, on-the-job training, and other soft skills workshops from the school administration. To address this issue, it would be essential for private school teachers, school administrators, and relevant stakeholders to collaborate and advocate for the importance of professional development. Additionally, government policies or initiatives that support and incentivize private schools to invest in teacher training and other professional development courses. The responses of all the respondents showed that job security and stability are big worries for them. The survey showed that private school teachers in Solukhumbu had a lot of uncertainty about job security and stability, which is creating stress for the teachers. The school management committee and school administrators should prioritize clear policies regarding employment terms, the school’s future plans, bonuses, insurance, retirement plans, disability coverage, and other wellness programs. All 16 respondents from different backgrounds responded that teaching is stressful and sensitive enough to address cultural differences, language barriers, and varying learning styles, which requires extra effort from the teacher. The school management committee and administration should prioritize the pressure of the sociocultural sensitivity of diverse students to the teachers. Limited participation in decision-making can generate stress by undermining teachers’ sense of professional value, autonomy, and job satisfaction. Addressing these stressors involves implementing effective feedback mechanisms by the concerned authorities that provide constructive insights, recognize achievements, and support teachers. Maslow’s theory is a psychological theory that suggests teachers are motivated by a hierarchy of needs, starting with basic needs and progressing through safety, belongingness, esteem, and self-actualization. While Maslow’s theory is primarily focused on motivation, it can be indirectly related to stress management. Implementing these recommendations requires the commitment of school administrators, policymakers, and educators to create a supportive and conducive environment for teaching and learning in private schools.